Implementasi Pengembangan Pojok Wirausaha Mahasiswa Sebagai Business Centre Berbasis Online Web Marketing Di Universitas Muhammadiyah Riau - Jusnita Jusnita; Siti Samsiah; Asrinda Amalia; Edo Aribe (LPPM UMRI, 2020)
The objectives of the Muhammadiyah Riau University (PPK UMRI) Entrepreneurship Development Program are to create new independent entrepreneurs based on web online marketing, increase the network between university entrepreneurship and industrial communities, and create entrepreneurship training methods that are suitable for UMRI students who already have businesses or are just starting out. effort. The approach method used in this activity is entrepreneurship and business training, entrepreneurship coaching, internships at partner companies, building networks and partnerships with partner companies, production and marketing management training, web-based online marketing business meetings and business consultations with guidance, supervision of tenants, tenant business financing techniques, patterns of providing technology assistance and problem solving methods. From this activity, results were obtained in the form of growing interest and motivation for student entrepreneurship, the creation of five new entrepreneurial students in the second year of 2020 who were ready to compete in the community, growing creativity and interest in students to form business entities, building networking between CSR funders and tenants of PPK UMRI students.